Visualizing charge separation in bulk heterojunction organic solar cells - Vithanage, Dimali Amarasinghe; Devižis, A; Abramavičius, Vytautas; Infahsaeng, Y; Abramavičius, Darius; MacKenzie, R C I; Keivanidis, Panagiotis E.; Yartsev, A; Hertel, D; Nelson, J.; Sundström, V; Gulbinas, V (My University, 2013)
Solar cells based on conjugated polymer and fullerene blends have been developed as a low-cost alternative to silicon. For efficient solar cells, electron-hole pairs must separate into free mobile charges that can be extracted in high yield. We still lack good understanding of how, why and when carriers separate against the Coulomb attraction. Here we visualize the charge separation process in bulk heterojunction solar cells by directly measuring charge carrier drift in a polymer:fullerene blend with ultrafast time resolution. We show that initially only closely separated (<1 nm) charge pairs are created and they separate by several nanometres during the first several picoseconds. Charge pairs overcome Coulomb attraction and form free carriers on a subnanosecond time scale. Numerical simulations complementing the experimental data show that fast three-dimensional charge diffusion within an energetically disordered medium, increasing the entropy of the system, is sufficient to drive the charge separation process.
Keywords: Solar cells; Conjugated polymer